Contextual factors influencing complex intervention research processes in care homes: a systematic review and framework synthesis. (1st March 2022) - Peryer, Guy; Kelly, Sarah; Blake, Jessica; Burton, Jennifer K; Irvine, Lisa; Cowan, Andy; Akdur, Gizdem; Killett, Anne; Brand, Sarah L; Musa, Massirfufulay Kpehe; Meyer, Julienne; Gordon, Adam L; et al.
Abstract: Background: Care homes are complex settings to undertake intervention research. Barriers to research implementation processes can threaten studies' validity, reducing the value to residents, staff, researchers and funders. We aimed to (i) identify and categorise contextual factors that may mediate outcomes of complex intervention studies in care homes and (ii) provide recommendations to minimise the risk of expensive research implementation failures. Methods: We conducted a systematic review using a framework synthesis approach viewed through a complex adaptive systems lens. We searched: MEDLINE, Embase, CINAHL, ASSIA databases and grey literature. We sought process evaluations of care home complex interventions published in English. Narrative data were indexed under 28 context domains. We performed an inductive thematic analysis across the context domains. Results: We included 33 process evaluations conducted in high-income countries, published between 2005 and 2019. Framework synthesis identified barriers to implementation that were more common at the task and organisational level. Inductive thematic analysis identified (i) avoiding procedural drift and (ii) participatory action and learning as key priorities for research teams. Research team recommendations include advice for protocol design and care home engagement. Care home team recommendations focus on internal resources and team dynamics. Collaborative recommendations apply to care homes' individual context and the importance of maintaining positive working relationships. Discussion: Researchers planning and undertaking research with care homes need a sensitive appreciation of the complex care home context. Study implementation is most effective where an intervention is co-produced, with agreed purpose and adequate resources to incorporate within existing routines and care practices.